Pharmacological action of Hedysarum polysaccharides: a review - Gao, Xiang; Ren, Chunzhen; Li, Linyu; Zhao, Huilin; Liu, Kai; Zhuang, Mengjie; Lv, Xinfang; Zhi, Xiaodong; Jiang, Hugang; Chen, Qilin; Zhao, Xinke; Li, Yingdong (Frontiers in Pharmacology, 2023)
Hedysarum, a traditional Chinese herbal medicine and food with a long history of clinical application, is used to improve health conditions and treat various diseases. Hedysarum polysaccharides (HPS), flavonoids, saponins, and alkaloids, are the primary components of Hedysarum. HPS is the most important natural active ingredient of Hedysarum, which has many pharmacological effects. Currently, HPS exhibits significant promise in drug development for various ailments such as tumors, diabetes, cardiovascular diseases, Alzheimer’s disease, and fibrosis. This review paper discusses the extraction, separation, and content determination techniques of HPS, along with the investigation of its chemical constituents. More importantly, we reviewed the anti-inflammatory pharmacological effects of HPS, such as inhibition of inflammatory factors and NF-κB signaling pathway; antitumor activity through apoptosis induction in tumor cells and blocking tumor cell proliferation and metastasis; antioxidant effects; regulation of various cytokines and immune cells; regulation of blood sugar levels, such as in type I and type II diabetes and in diabetic complications; improvement in symptoms of Alzheimer disease; anti-aging and anti-fibrosis properties; and improvement in cerebral ischemia-reperfusion injury. This review paper establishes the theoretical foundation for future studies on the structure, mechanism, and clinical use of HPS.